The Effectiveness of Zoledronic Acid and Ibandronic Acid in Delaying Skeletal-Related Events in Multiple Myeloma in Indonesia - Nutrisia Aquariushinta Sayuti; Tri Murti Andayani; Dwi Endarti; Kartika Widayati (Faculty of Pharmacy, Universitas Gadjah Mada)
Zoledronic acid and ibandronic acid are listed in the Indonesian national formulary to prevent skeletal-related events (SRE) in patients diagnosed with bone metastasis in multiple myeloma (MM), with limited evidence to compare their effectiveness. This study aimed to investigate the effectiveness and safety of zoledronic acid and ibandronic acid in delaying SRE. The method was the retrospective, with data obtained from the multicenter study for MM patients with bone metastasis (aged over 18 years), based on medical records between January 2016 and December 2018. Patients were assigned to zoledronic acid and ibandronic acid groups. The clinical outcome was the next SRE which consists of vertebral/bone fracture, spinal cord compression leading to the need for surgery or radiation, and adverse event (AE) due to 2 years of drugs usage. Result of this research was made up of a total of seventy (70) patients with 40 in the zoledronic acid group, and 30 in ibandronic acid. At median treatment duration of 8 months (range: 2 – 24 month), SRE incident in zoledronic acid and ibandronic acid were 20.0 % and 23.3 % respectively. Furthermore, their mean SRE free survival times were 21 months [95% confidence interval (CI) 19 - 23 months], and 19 months [95% CI, 16 – 22 months], respectively. Also, their time intervals were not significantly different (p>0.05). The osteonecrosis of the jaw (ONJ) was AE which occurred more in zoledronic acid than ibandronic acid. The conclusion was zoledronic acid tends to delay SRE time compared to ibandronic acid, although more ONJ occur.